Giving Compliments in Tonight Show Net Tv and The Tonight Show Starring Jimmy Fallon: Cross-Cultural Pragmatics - Novitasari, Ainia Arum (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2024)
This study aims to investigate giving compliments used by the host of the Tonight Show Net TV and the Tonight Show Starring Jimmy Fallon in cross-cultural pragmatics. This study will compare two different cultures, American and Indonesian cultures. Indonesia follows the Eastern culture, while America holds the Western culture. These two cultures are fascinating subjects of research on giving compliments. The researcher chose the theory of giving compliments from Searle (1979) in order to establish which strategy had been used by both cultures. This study used the descriptive qualitative method. After applying the theory to data, the researcher discovered that there was a difference between these two cultures in their form of giving compliments. Indonesia and America, however, do have similar results in giving compliments such as using the adjectives words such as ‘beautiful’, ‘fantastic’, ‘great’, ‘good’, ‘nice’, ‘excellence’, and ‘amazing’.